2005
DOI: 10.1038/sj.emboj.7600542
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hematopoietic reserves in DNA interstrand crosslink repair-deficient Ercc1−/− mice

Abstract: The ERCC1-XPF heterodimer is a structure-specific endonuclease involved in both nucleotide excision repair and interstrand crosslink repair. Mice carrying a genetic defect in Ercc1 display symptoms suggestive of a progressive, segmental progeria, indicating that disruption of one or both of these DNA damage repair pathways accelerates aging. In the hematopoietic system, there are defined age-associated changes for which the cause is unknown. To determine if DNA repair is critical to prolonged hematopoietic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 59 publications
6
99
0
Order By: Relevance
“…Recently, it was reported that Ercc1 −/− mice also display hematopoietic aging as both basal hematopoiesis and reserve capacity under stress were severely reduced in these mice, consistent with that found in normal aged mice [102]. However, the premature liver polyploidy, as was reported in Ercc1 −/− mice, differs from the normal aging-related process, as the observed dramatic increased p21 levels in Ercc1 −/− livers were absent in livers of normal aging mice with the same amount of polyploidy [103].…”
Section: Many Of the Features Of The Ercc1supporting
confidence: 63%
“…Recently, it was reported that Ercc1 −/− mice also display hematopoietic aging as both basal hematopoiesis and reserve capacity under stress were severely reduced in these mice, consistent with that found in normal aged mice [102]. However, the premature liver polyploidy, as was reported in Ercc1 −/− mice, differs from the normal aging-related process, as the observed dramatic increased p21 levels in Ercc1 −/− livers were absent in livers of normal aging mice with the same amount of polyploidy [103].…”
Section: Many Of the Features Of The Ercc1supporting
confidence: 63%
“…As more fully described in recent reviews, DNA damage has been linked to stem cell attrition in a number of experimental contexts (Blasco, 2007;Rando, 2006;Sharpless and DePinho, 2007). Perhaps most relevant to the two NER papers discussed here, Prasher et al (Prasher et al, 2005) have shown that 3 week old Ercc1-/-mice exhibit multilineage cytopenia and fatty replacement of bone marrow, similar to old wild type mice. Moreover, hematopoietic progenitor numbers and proliferative reserves were dramatically decreased in the Ercc1-/-mice compared to their wild type counterparts.…”
Section: How Does the Dna Damage Response Affect Tissue Homeostasis?mentioning
confidence: 84%
“…Furthermore, in the absence of XPF-ERCC1 there is a defect in recruitment of FANCD2 to chromatin [116]. Most compellingly, the phenotype of Ercc1-deficient mice has significant overlap with FA exhibiting growth retardation, blood cytopenias, developmental defects and sterility [113,117,118]. It is important to note that the sterility observed in Ercc1-deficient mice is a pattern of primordial germ cell failure the unifying feature of all FA mouse models [118].…”
Section: A Specific Molecular Defect In Fanconi Anaemiamentioning
confidence: 99%